Utilization and benefits of point-of-care testing in primary healthcare⁠ - Jumah, Mohammed A.; Magliah, Fisal F.; Ageel, Salman A.; Almutairi, Jouri A.; Alsubhi, Wed A.; Alamer, Shorouq A.; Alanazi, Maryam A.; Alanazi, Hejris J.; Alshaqha, Rayan F.; Almoghrabi, Dania M.; Alyusef, Ali A.; Alkinani, Hajer I. (International Journal Of Community Medicine And Public Health, 2025)
Point-of-care testing (POCT) represents a transformative advancement in healthcare, enabling rapid and accurate diagnostics at or near the site of patient care. By reducing reliance on centralized laboratories, POCT expedites clinical decision-making and enhances healthcare delivery, particularly in underserved regions. Its application spans various medical fields, including infectious diseases, chronic disease management, and emergency care. Innovations such as molecular diagnostics, biosensors, and artificial intelligence (AI) integration have improved the precision, reliability, and accessibility of POCT devices, offering significant benefits for patient outcomes and healthcare efficiency. POCT has demonstrated its potential to reduce diagnostic delays, lower hospital admissions, and decrease the burden on overextended healthcare systems. Rapid diagnostics for conditions such as acute myocardial infarction, diabetes, and malaria have resulted in timely interventions, improving survival rates and reducing complications. In addition to clinical benefits, economic analyses highlight the cost-effectiveness of POCT, as it minimizes resource utilization and shortens patient treatment cycles. However, challenges persist in scaling POCT accessibility. Financial barriers, supply chain limitations, regulatory inconsistencies, and workforce training deficits impede its widespread adoption, particularly in low- and middle-income countries. Addressing these issues requires innovative funding models, global regulatory harmonization, and capacity-building initiatives to empower healthcare workers. Technological advancements continue to expand POCT's potential, integrating real-time diagnostics with digital health platforms and epidemiological surveillance systems. These developments promise not only to enhance healthcare delivery but also to improve public health responses to outbreaks and health crises. By bridging the gap between diagnostics and treatment, POCT offers a pathway to more equitable and efficient healthcare systems, transforming how and where care is delivered. Its integration into healthcare frameworks holds the potential to redefine patient care, fostering a future of accessible, high-quality healthcare for all.